PENINGKATAN HASIL BELAJAR SISWA PADA PENCERMINAN BANGUN DATAR MENGGUNAKAN PAPAN BERPAKU DI KELAS IV - Budiman, Urip; Sabri, Tahmid; Kartono, Kartono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this research is whether by using manipulated media spikes can improve student learning outcomes in the reflection material flat build in class IV 41 Primary School, North Pontianak. The method used is descriptive method in the form of classroom action research. The research subjects were the teacher as a researcher and fourth grade students totaling 27 people. The research procedure consisted of planning, implementing, observing and reflecting. The data collected is the score of the teacher's ability to plan and implement learning analyzed with average calculations. Data collection techniques with direct observation and measurement through observation sheets and tests. The results of the study in the first cycle obtained an average score of the ability of teachers to design learning by 3.09 and in the second cycle increased by 0.83 to 3.92. The ability of teachers to implement learning in the first cycle was 2.80 and in the second cycle increased by 1.03 to 3.83. Mastery learning students in the first cycle of 71.09 and in the second cycle increased by 27.06 to 98.15. Thus, the use of spike board manipulative media can improve the learning outcomes of students in grade IV 41 Primary School, North Pontianak.Â Keywords:Improvement, learning outcomes, manipulative media